Prostaglandin Induced labor a risk factor for cervical tear - Devkota, Ashok; Adhikari, Silu; Neupane, Bhanu (Nepal Journal of Obstetrics and Gynaecology, 2009)
<!--[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if !mso]> <![endif]--> <!--[if gte mso 10]> <![endif]--> Objective: To determine risk factors associated with cervical tear. Method: Design: Retrospective analysis of obstetric variables in 116 women who had sustained cervical tear. Setting: Obstetric Department of Tribhuwan University Teaching Hospital, Kathmandu, Nepal. Subjects: This study identified 9662 vaginal deliveries over 42 months period from April 2003 to September 2006 from obstetric records. One hundred and sixteen cases who sustained cervical tear were selected and different variables were analyzed. Results: Overall rate of cervical tear was 1.20% (n=116) of which 64.7% (n=75) occurred in primi and 35.3% (n=41) in multipara. It was associated with induced labor in 21.2 % [with dinoprostone gel (cerviprime) 16.4% (n= 17) and misoprostal in 4.8% (n=5) respectively]. Augmentation with oxytocinon (syntocinon) had been done in 51.9% (n=54 cases). Mean age of parturient was 24.3 years and average birth weight of baby was 3.21kg. Cervical injury occurred more in post-dated delivery [35% (n=42)], compared to pre term delivery [6.9% (n=8)]. Average duration of second stage was 35.2 minutes. Episiotomy was given in 73 / 116 (66%) and not many of the cervical tear was associated with instrumental delivery: [forceps 0.96% (n=1) and ventouse 3.85% (n=4)]. There were 10 cases of postpartum haemorrhage. Conclusion. From the view point of limited number of published studies on cervical tear pertaining to vaginal delivery where locally used prostaglandins have not been identified as a major risk factor in contrary to our study findings where every sixth case have been implicated, a cautious prelabour induction with forward anticipation of traumatic PPH as recognized here is worthwhile. Key words: Cervical tear, dinoprostone gel (cerviprime) and misoprostal, induction of labour doi:10.3126/njog.v1i2.1488 N. J. Obstet. Gynaecol Vol. 1, No. 2, p. 14 - 18 Nov-Dec 2006